A review of recent advances in anesthetic drugs for patients undergoing cardiac surgery - Sun, Yutian; Sun, Xiangyou; Wu, Haibo; Xiao, Zhaoyang; Luo, Wei (Frontiers in Pharmacology, 2025)
Inducing and maintaining general anesthesia requires a diverse set of medications. Currently, heart surgery anesthetic management does not adhere to any one standard protocol or set of drugs. To ensure steady circulatory function while providing sufficient sedation, anesthetic medications are carefully selected for cardiovascular operations. Among the opioids used most often in cardiac surgery are fentanyl, sufentanil, and remifentanil. As a cardiac anesthesiologist, your key responsibilities will be to maintain your patient’s blood pressure (BP) and oxygen levels, reduce the frequency and intensity of ischemia events, and make it easy for them to get off of cardiopulmonary bypass (CPB) and supplemental oxygen fast. Additionally, new knowledge gaps have been identified as a result of developments in cardiac anesthetics, which must be addressed. The goal of the most recent developments in cardiac anesthesia has been to decrease risks and increase accuracy in patient outcomes during cardiac surgeries. Furthermore, new methods and tools are contributing to the evolution of cardiovascular anesthesia toward a more dynamic, patient-centered approach, with an eye on boosting safety, decreasing complications, and facilitating better recovery for patients. New medications and methods have emerged in the field of anesthetic pharmacology, aiming to improve anesthesia management, particularly for patients who have cardiovascular disease. Optimal cardiovascular stability, fewer side effects, and enhanced surgical recovery are achieved by use of these medications. We have reviewed all the different kinds of cardiac anesthetic techniques and medications in this research. We have also examined the many new anesthetic medicines that have been produced and used for individuals with cardiovascular issues. Next, we covered prospects in the realm of cardiovascular anesthesia and novel cardiac anesthetic drugs.